PENYEBAB DAN ALTERNATIF MITIGASI BENCANA BANJIR DI GRESIK SELATAN (Universitas Muhammadiyah Palembang, 2022)
One of problems that often occur in Gresik Regency in Gresik City is Floods. As a result of flood, the biggest impact occurred in the Districts of Cerme, Benjeng, Menganti, and Balongpanggang. The research has a purpose, namely, to find out what factors cause flooding in the South Gresik City Region. The methods used are interviews and questionnaires. Interviews were used to determine the type of flood mitigation that was suitable for the southern Gresik City area. While the questionnaire was given to determine the appropriate mitigation according to the existing conditions in the area or the factors causing flooding in the southern Gresik City area. Mixed Methods were used to collect data with qualitative and quantitative data types. Qualitative data was conducted through direct observation and interviews. While the quantitative data was obtained from questionnaire results. From the results of the analysis using Nvivo 12 plus©, the cause of flooding that often occurs in Gresik City is caused by the overflow of the Lamong River. Rather than that caused by the river experiencing siltation. This causes runoff to overflow. Mitigation is one thing that can be done when there is a flood in the southern Gresik City area. Analytic Hierarchy Process (AHP) is a river improvement and regulation system which includes benchmarks with the highest yield of 0.558. The best alternative is River improvement, namely river dredging with a weight of 0.404.